“A Critical Study on Methods and Protagonists of Literary Criticism by Gino Tellini” - Fatemeh Asgari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Literary criticism, as a special branch of humanities and social sciences, is one of the most important topics in foreign literary studies and therefore mostly focused at the universities all around the world. Although the comprehension of literary and intellectual theories in its own historical contexts does not seem always simple. In Iranian universities the history of criticism is abundantly studied too, and so many useful works in this case have been translated into Persian and are used by academic staffs and students today. The book presented here is recommended for the literary criticism in Italian language and literature course. However, the main flaw of this book, according to this paper, might be the lack of a detailed historical and methodical introduction about theories of literary criticism. Then some suggestions are given to improve these aspects.